Amygdala reactivity predicts adolescent antisocial behavior but not callous-unemotional traits. (April 2017) - Dotterer, Hailey L.; Hyde, Luke W.; Swartz, Johnna R.; Hariri, Ahmad R.; Williamson, Douglas E.
Highlights: Greater amygdala reactivity to angry faces predicted youth antisocial behavior. Callous-unemotional traits were not related to amygdala reactivity. Findings were similar across sex, ethnicity, and pubertal stage. Abstract: Recent neuroimaging studies have suggested divergent relationships between antisocial behavior (AB) and callous-unemotional (CU) traits and amygdala reactivity to fearful and angry facial expressions in adolescents. However, little work has examined if these findings extend to dimensional measures of behavior in ethnically diverse, non-clinical samples, or if participant sex, ethnicity, pubertal stage, and age moderate associations. We examined links between amygdala reactivity and dimensions of AB and CU traits in 220 Hispanic and non-Hispanic Caucasian adolescents (age 11–15; 49.5% female; 38.2% Hispanic), half of whom had a family history for depression and thus were at relatively elevated risk for late starting, emotionally dysregulated AB. We found that AB was significantly related to increased right amygdala reactivity to angry facial expressions independent of sex, ethnicity, pubertal stage, age, and familial risk status for depression. CU traits were not related to fear- or anger-related amygdala reactivity. The present study further demonstrates that AB is related to increased amygdala reactivity to interpersonal threat cues in adolescents, and that this relationship generalizes across sex, ethnicity, pubertal stage, age, and familial risk status for depression.